Metal complexes of a calix[4]arene diamide: Syntheses, crystal structures and molecular mechanics calculations on [Fe(L(1)-2H)][FeCl4] and [Er(L(1)-2H)(picrate)] (L(1)=5,11,17,23-tetra-tert-butyl-25,27-bis(diethylcarbamoylmethoxy)calix[4]arene) - Beer, P; Drew, M; Leeson, P; Ogden, M (1996)
Reactions of 5,11,17,23-tetra-tert-butyl-25,27-bis(diethylcarbamoylmethoxy)calix[4]arene (L1) with metal salts have been found to produce 1:1 metal/calixarene complexes. The rigid nature of the lower rim of the calix[4]arene in the cone conformation ensures that four donor oxygen atoms are approximately coplanar thus ruling out any possibility of orthogonal coordination and restricting the types of metals that form complexes. Complexes with Fe(III) and Er(III) are reported and structurally characterised. The crystal structure of the complex [Fe(L1-2H)](FeCl4) has been determined. The metal coordination sphere shows a trigonal prismatic environment with the metal bonded to two phenolic and two ethereal oxygen atoms at the bottom of the rim and to two carbonyl oxygen atoms, Molecular mechanics calculations show that the cavity is ideally suited to this type of coordination sphere. The lanthanide complex [Er(L1-2H) (picrate)] has a similar structure but the metal is eight coordinate being bonded to the six oxygen atoms of the calix[4]arene diamide and also to a bidentate picrate anion.